2008
DOI: 10.1080/00016340802428146
|View full text |Cite
|
Sign up to set email alerts
|

Reference values for α1‐acid glycoprotein, α1‐antitrypsin, albumin, haptoglobin, C‐reactive protein, IgA, IgG and IgM during pregnancy

Abstract: The objective of this study was to establish reference intervals and decision limits for the interpretation of the acute phase proteins alpha(1)-acid glycoprotein (orosomucoid), alpha(1)-antitrypsin, C-reactive protein (CRP), haptoglobin and albumin, IgA, IgG and IgM during pregnancy by longitudinal sampling from 52 healthy women with normal pregnancies. Each woman was sampled in weeks 7-17; weeks 17-24; weeks 24-28; weeks 28-31; weeks 31-34; weeks 34-38 and predelivery (-14-0 days prior to delivery) and postp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
67
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 16 publications
10
67
0
1
Order By: Relevance
“…In the present study, we showed that CRP levels significantly increased between the first trimester and mid-pregnancy, before stabilizing. Our results are consistent with those reported by Larsson et al, 19 who showed an increase in CRP levels until weeks 24 to 28 of uncomplicated pregnancy and a relative stabilization after this period. We initially hypothesized that maternal diabetes status may have some influence on CRP levels, as this was previously described in nonpregnant populations (both women and men).…”
supporting
confidence: 83%
“…In the present study, we showed that CRP levels significantly increased between the first trimester and mid-pregnancy, before stabilizing. Our results are consistent with those reported by Larsson et al, 19 who showed an increase in CRP levels until weeks 24 to 28 of uncomplicated pregnancy and a relative stabilization after this period. We initially hypothesized that maternal diabetes status may have some influence on CRP levels, as this was previously described in nonpregnant populations (both women and men).…”
supporting
confidence: 83%
“…A high prevalence of infection and/or inflammation, indicated by elevated CRP, was also reported among 150 anaemic pregnant women in Malawi as mean CRP concentration was 30 mg/l and 35 % had elevated CRP (CRP >190 nmol/l (19·5 mg/l)) (7) . Although CRP increases during normal pregnancy (55,56) , these findings in pregnant women in Africa indicate higher concentrations than in other populations. Furthermore, a study in the USA reported that while median CRP was 4·8 mg/l during pregnancy, black race was independently associated with serum CRP levels greater than the 75th percentile (15·7 mg/l) (57) .…”
Section: Discussionmentioning
confidence: 69%
“…Hepatocytes are also responsible for IL-1/IL-6-inducible AAT production during inflammation. Levels of AAT also increase in the circulation during normal pregnancy (17) and in the process of aging (18). The half-life of AAT in the circulation is 3-5 d (16).…”
Section: An Overview Of α 1 -Antitrypsinmentioning
confidence: 99%
“…AAT rises during normal pregnancy (17). An intriguing association appears to exist between AAT inactivity and preterm premature rupture of membranes.…”
Section: Pregnancy Complicationsmentioning
confidence: 99%